Denarna terjatev delavca iz delovnega razmerja kot predmet odstopa in drugih poslov s primerljivimi učinki - Juhart, Miha (Podjetje in delo, 2014)
The author discusses legal problems of the disposal with claims deriving from the employment. The employee gains different claims (salary and other claims) that are one of the most important part of his property. Therefore it is the interest of the employee to dispose with them to secure his future obligations to his creditors. The disposal with these claims is limited by legal rules in Execution Law to ensure the existence of the employee and his family. The wording of the rule is not clear enough and opens the space for different interpretations. The word is about the assignment and pledge of these claims in advance. In literature and jurisprudence there are very different statements, if the claims are allowed to assign in full or with the mentioned limitations. By authors opinion the limitations should be considered by any disposal in advance. On the other hand after the maturity of the claim there are no more needs to protect the living minimum of the employee, what also means that there is no more need to impose the limitations.
Keywords: cesija; delovna razmerja; plače; prenos; terjatve; zastavna pravica